MEMBANGUN GENERASI YANG CERDAS DAN MANDIRI DALAM MENGELOLA UANG - Ni Made Mila Rosa Desmayani; Luh Gede Bevi Libraeni; Ni Putu Eka Kherismawati; Kadek Nonik Erawati; Ida Bagus Putu Meisa Pratama Putra (PUAN INDONESIA, 2026)
This community service program addressed the low level of financial literacy among adolescents at Posyandu Remaja Pejeng Kawan, Gianyar. Limited understanding of money management, inability to distinguish needs from wants, lack of saving habits, and absence of simple financial records indicated an urgent need for structured financial education. Strengthening financial literacy at an early age is essential to prevent consumptive behavior and to foster responsible financial attitudes in adulthood. The program was implemented through systematic stages, including observation, problem identification, training, evaluation, and reporting. A participatory approach was applied using interactive discussions, case examples, simple financial recording simulations, and a seven-day saving challenge. Evaluation was conducted qualitatively through observation of participation, reflective discussions, and assessment of participants’ ability to explain and practice the concepts learned. The results indicate improved understanding of money functions, clearer differentiation between needs and wants, increased awareness of saving, and initial practice of recording daily expenses. The program also strengthened the role of the youth health post as a life-skills development platform. Overall, the activity demonstrates that participatory financial education effectively enhances adolescents’ financial awareness and supports the formation of responsible financial behavior.